High frequency functional brain networks in neonates revealed by rapid acquisition resting state fMRI. Issue 7 (18th March 2015) - Smith‐Collins, Adam P.R.; Luyt, Karen; Heep, Axel; Kauppinen, Risto A.
Abstract Understanding how spatially remote brain regions interact to form functional brain networks, and how these develop during the neonatal period, provides fundamental insights into normal brain development, and how mechanisms of brain disorder and recovery may function in the immature brain. A key imaging tool in characterising functional brain networks is examination of T2*‐weighted fMRI signal during rest (resting state fMRI, rs‐fMRI). The majority of rs‐fMRI studies have concentrated on slow signal fluctuations occurring at <0.1 Hz, even though neuronal rhythms, and haemodynamic responses to these fluctuate more rapidly, and there is emerging evidence for crucial information about functional brain connectivity occurring more rapidly than these limits. The characterisation of higher frequency components has been limited by the sampling frequency achievable with standard T2* echoplanar imaging (EPI) sequences. We describe patterns of neonatal functional brain network connectivity derived using accelerated T2*‐weighted EPI MRI. We acquired whole brain rs‐fMRI data, at subsecond sampling frequency, from preterm infants at term equivalent age and compared this to rs‐fMRI data acquired with standard EPI acquisition protocol. We provide the first evidence that rapid rs‐fMRI acquisition in neonates, and adoption of an extended frequency range for analysis, allows identification of a substantial proportion of signal power residing above 0.2 Hz. We thereby describe changes in brain connectivity associated with increasing maturity which are not evident using standard rs‐fMRI protocols. Development of optimised neonatal fMRI protocols, including use of high speed acquisition sequences, is crucial for understanding the physiology and pathophysiology of the developing brain. Hum Brain Mapp 36:2483–2494, 2015. © 2015 Wiley Periodicals, Inc.